Improved electric property in SrTiO3–Bi2NiMnO6–SrTiO3 sandwich structural thin films. (September 2015) - Zhang, T.F.; Tang, X.G.; Liu, Q.X.; Jiang, Y.P.; Lai, J.L.
Highlights: Bi2 NiMnO6 thin film was prepared by the chemical solution deposition method. The room temperature ferroelectric of Bi2 NiMnO6 was obtained. SrTiO3 was selected as buffer layer which significantly reduced the leakage current density. Asymmetrical curve of leakage current characteristics was observed and analyzed. Abstract: Bi2 NiMnO6 thin film was grown on Pt(1 1 1)/Ti/SiO2 /Si(1 0 0) substrates with and without SrTiO3 buffer layer by the chemical solution deposition method. Room temperature ferroelectric and leakage current characteristics were investigated. A typical ferroelectric hysteresis loop could be clearly seen, which suggested the existence of the room temperature ferroelectric. Leakage current results indicated that electrical properties of Bi2 NiMnO6 thin films were strongly related to SrTiO3 buffer layers, SrTiO3 buffer layers significantly reduced the leakage current density. Asymmetrical curves of leakage current density were observed and analyzed. When the Au electrode was biased negatively, the Au/Bi2 NiMnO6 and Au/SrTiO3 /Bi2 NiMnO6 interfaces formed Ohmic contacts. Space-charge-limited behavior became dominant at high electric voltage when the Bi2 NiMnO6 /Pt and Bi2 NiMnO6 /SrTiO3 /Pt interfaces were biased negatively.